Multielemental alloying of steel surface layer under the action of compression plasma flows; Journal of Physics: Conference Series; Vol. 1238 : Laser and plasma research and technologies - LaPlas 2018 - Cherenda N. Nikolay; Uglov V. V. Vladimir Vasilievich; Dzagnidze G. M.; Astashinsky V. M. Valentin Mironovich; Kuzmitsky A. M. Anton Mikhaylovich (2019, 2019)
Title screen